Application of Incung Kerinci Script on Metal Media - Yosan Novendra (Journal of Social Research, 2023)
Incung script is a script that belongs to the Malay type. This type of script is commonly referred to as kaganga. that is a script that was born and developed in the upper reaches of rivers in the interior. The Incung script is used after the pallawa script. The Incung Kerinci script itself is formed by straight, broken lines, and curved Incung Kerinci script is a relic of ancient Kerinci ancestors. Incung Kerinci was used by Kerinci's ancestors to document history, literature, customary law, and mantras. The concept of creating this work departs from the Incung Kerinci script as a writing medium on metal works. The theoretical foundations used as guidelines in the embodiment of this work use the theoretical foundations of form, function, and aesthetics. This method of creating works uses three stages, ranging from exploration, design, and embodiment. The materials used in making this work are iron plates, copper plates, brass plates, and oil paints. The techniques used are welding, inlay, and scroll techniques. The shape of this work is three-dimensional and two-dimensional in the form of seven works, this work has a practical function, namely decorative lights, decorative clocks, and two display works with the application of the Incung Kerinci script with metal media.